Latent Effects from Low Salinity Stress and the Interactive Influence of Temperature and Salinity on Larval and Juvenile Growth in the Marine Gastropod Crepidula Fornicata. - Bashevkin, Samuel M. (Tufts Archival Research Center, 2014)
Abstract: Sea surface temperatures have been rising and are predicted to continue rising in coming years because of global warming. In addition, salinity has been decreasing in high latitudes and is expected to continue decreasing due to altered precipitation patterns and glacial melting caused by climate change. Many marine organisms that are adapted to the present conditions may be drastically affected by these oceanic changes. Early life stages will be especially susceptible, since they do not yet have fully developed adult defenses. In this study, we investigated the effects of reduced salinity (20 psu and 30 psu control) and altered temperature (15, 20, 25, and 29°C) on the growth, percent inorganic content (representing calcification), and feeding rates of juveniles and larvae of the invasive snail Crepidula fornicata. Both larval and juvenile growth rates were significantly depressed by low salinity and elevated by higher temperatures. The salinity that snails were exposed to as larvae significantly impacted juvenile growth rates in 4 out of 6 experiments, an example of latent effects, but the magnitude and direction of this effect depended on temperature and parentage. In addition, juvenile feeding rates were significantly depressed in low salinity but there was little change in percent inorganic content. Larval percent inorganic content at 20°C was 27% lower in 20 than in 30 psu. In conclusion, C. fornicata may experience more favorable conditions in a warmer future: growth rates will increase, probably making juveniles more resistant to predation. However, in regions where salinity is decreasing, C. fornicata juveniles will grow and feed more slowly, thereby increasing predation risk by forcing them to spend more time at more vulnerable smaller sizes. Thus, the future of C. fornicata and their potential to continue invading will depend on the specific salinity and temperature conditions they are exposed to during larval and juvenile development.